Nitrogen‐doped graphene prepared by thermal annealing of fluorinated graphene oxide as supercapacitor electrode. Issue 11 (21st August 2019) - Jiang, Fei; Zhang, Jixiang; Li, Nian; Liu, Cui; Zhou, Yongqiang; Yu, Xinling; Sun, Lidong; Song, Yanping; Zhang, Shudong; Wang, Zhenyang
Abstract: BACKGROUND: Nitrogen doping significantly improves the electrochemical properties of graphene. Here, a new and effective methodology of preparing nitrogen‐doped graphene (NG) by thermal annealing of fluorinated graphene oxide (FGO) under the atmosphere of ammonia, is reported, in which ammonia is the reductant for FGO reduction and also the nitrogen source for nitrogen doping. This method can achieve higher nitrogen doping content than conventional approaches. RESULTS: FGO prepared from fluorinated graphite polymer (CF) is directly used as a precursor to synthesize NG. Four samples with the same reaction time and different annealing temperatures are compared, and the highest nitrogen content of the NG reaches 12.45 at% at the reaction condition of 800 °C and 3 h. The synthesized NG samples are examined as a supercapacitor electrode material, displaying excellent performance due to the high nitrogen doping and a large number of active sites. CONCLUSION: With the increase of annealing temperature, the nitrogen content of different NG samples first increases and then decreases. The specific capacitance of NG electrode material also shows the same trend as the nitrogen content. The highest specific capacitance in three‐electrode configuration attains 225.2 F g −1 at a current density of 1 A g −1 . The electrode maintains a 90% capacitance after 5000 cycles, showing good cycle stability. This synthetic method provides a new approach for the preparation of NG with high nitrogen doping as supercapacitor electrode materials. © 2019 Society of Chemical Industry